Design and Analysis of a Ten-Passenger Electric Aircraft Named Djinn - Mulyanto, Taufiq; K Musyahada; F Carakapurwa; F Jatmiko; C Puspaningtyas; F Hanafi; Huda, Zulmiftah; Hamdani, Fadil (Journal of Applied Science, Engineering and Technology, 2024)
As aircraft industries contribute more than 12% of the carbon emission globally, the urgency to develop a more sustainable and reliable source of energy to power aircrafts has become greater. Regarding that concern, an electric-powered aircraft is proposed to become the solution for the search of green technology. An electric aircraft has been proven to be capable of reducing carbon emission and sound emission. Despite of the advantages, the use of electric aircraft is still very scarce since there are a lot of considerable issues such as low energy density power sources, reliability problems, and the lack of design references. As a contribution for the development process, an electric aircraft by the name of “Djinn” has been designed, in hope that this aircraft can be an addition to the references for future endeavors. The methods used for designing the aircraft is similar as the methods used for developing conventional aircrafts, with slightly modified approximation and assumptions.